The Influence of Financial Literacy, Locus Of Control and Lifestyle on Cashless Society Behavior of Gen Z in Pontianak City - Syifa Azizah; Heni Safitri; Dedi Hariyanto (www.amertainstitute.com, 2025)
The purpose of this study is to investigate the impact of financial literacy, locus of control, and lifestyle on the cashless society behavior of Generation Z in Pontianak City. This study employs quantitative methodologies. Pontianak City's Generation Z population was researched. The study sample was chosen using a purposive sampling method, in which the sample was chosen based on certain characteristics requested by the researcher. This survey had a total of 100 respondents. The outcomes of the study suggest that financial literacy has a positive and significant influence on cashless society behavior. On the other hand, locus of control has a negative and minor influence on cashless society behavior. And lifestyle has a favorable and important influence on cashless society behavior.